2012
DOI: 10.1002/nbm.2770
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the dentin‐pulp complex response to caries by ADC mapping

Abstract: The prognostic potential of apparent diffusion coefficient (ADC) mapping was studied as complemented by high-resolution 3D T(1)-weighted MRI in the assessment of dentin-pulp complex response to caries. Twenty-six extracted human teeth, with or without caries lesions of different grades in accord with the International Caries Detection and Assessment System (ICDAS), were analyzed by high-resolution MRI at 2.35 T. A signal rise in demineralized hard dental tissues in high-resolution T(1)-weighted MR images enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Nevertheless, the ACAD profile with standard deviations always fell within the range of those in NCAD, and the type of caries-affected dentin was not a statistically significant factor when comparing mineral density at different lesion levels. It should be noted that the NCAD lesions greatly vary in depth depending on the activity of the lesion and the time that dentin was subjected to the caries process; indeed caries may affect the whole thickness of dentin from dentinenamel junction through to the pulp 17) . The ACAD in the current study was compared to NCAD superficially (up to 150 µm), because in terms of the bonding interface with restorative materials, only this zone plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the ACAD profile with standard deviations always fell within the range of those in NCAD, and the type of caries-affected dentin was not a statistically significant factor when comparing mineral density at different lesion levels. It should be noted that the NCAD lesions greatly vary in depth depending on the activity of the lesion and the time that dentin was subjected to the caries process; indeed caries may affect the whole thickness of dentin from dentinenamel junction through to the pulp 17) . The ACAD in the current study was compared to NCAD superficially (up to 150 µm), because in terms of the bonding interface with restorative materials, only this zone plays a role.…”
Section: Discussionmentioning
confidence: 99%
“…Its use produced a nearly perfect linear relation to ICDAS scores, i.e. the higher the average ADC value, the lower the ICDAS score [Vidmar et al, 2012]. It must also be noted that the time involved for ADC mapping -equal to one and a half hours in our study -is still too long for in vivo use.…”
Section: Discussionmentioning
confidence: 85%
“…Before extraction all caries lesions were clinically examined using the visual-tactile method and recorded as active following the scores and criteria used by Ekstrand et al [1998]. The teeth were immersed in a physiological solution (pH ≈ 7.4) immediately after extraction and subsequently stored in a neutral buffered 10% formalin solution (Sigma-Aldrich, Germany) at 8 ° C in order to avoid autolysis in the pulp [Vidmar et al, 2012]. In order to prevent dental pulp desiccation during long scanning time as well as to visualize the tooth surface, the teeth were coated with the two-component silicone dental impression material Exaflex ® (GC, Japan) prior to MR acquisition.…”
Section: Human Teethmentioning
confidence: 99%
See 1 more Smart Citation
“…4 , 22 One of most recent MRI studies demonstrated that caries affected also dental pulp by changing its diffusion properties. 23 …”
Section: Introductionmentioning
confidence: 99%